Rechargeable Batteries for Renewable Energy: Current Status, Technical Challenges, and Future Directions - Hu Qihan (E3S Web of Conferences)
With the increasing severity of climate change and the threat of global warming, countries are boosting the development and promotion of renewable energy sources like solar and wind to bring about the energy transition and reduce carbon emissions. However, because these energy sources are unreliable in supply, efficient energy storage technologies are required to balance energy output to satisfy daily electricity demand. Among numerous energy storage alternatives, rechargeable battery technology has received a lot of interest due to its high energy density, efficiency, and reusable nature. Currently, lithium-ion batteries, nickel-metal hydride batteries, lead-acid batteries, and other rechargeable battery types are widely utilized in consumer electronics, transportation, renewable energy storage, medical equipment, and other industries. This paper examines the basic working principle, structure, and important chemical reactions of rechargeable batteries, as well as their performance indicators such as capacity, energy density, cycle life, and so on. Furthermore, this paper addresses the technology’s global application cases, as well as the status of its development and the major problems, such as safety, cost, longevity, environmental impact, and other issues. Finally, this article examines probable future technology breakthroughs, market trends, and the possibility of suitable policy support in this field.